Death, happiness, and the calculation of compensatory damages - Andrew J. Oswald; Nattavudh Powdthavee (Institute for the Study of Labor (IZA), 2007)
This paper studies the mental distress caused by bereavement. The largest emotional losses are from the death of a spouse; the second-worst in severity are the losses from the death of a child; the third-worst is the death of a parent. The paper explores how happiness regression equations might be used in tort cases to calculate compensatory damages for emotional harm and pain-and-suffering. We examine alternative well-being variables, discuss adaptation, consider the possibility that bereavement affects someone's marginal utility of income, and suggest a procedure for correcting for the endogeneity of income. Although the paper's contribution is methodological, and further research is needed, some illustrative compensation amounts are discussed.
Keywords: D1; 340; Bereavement; damages; happiness; compensation; well-being; GHQ scores; Lebenszufriedenheit; Sterblichkeit; Familie; Wert des Lebens; Schätzung; Großbritannien